Reduction of Cogging Torque in AFPM Machine Using Elliptical-Trapezoidal-Shaped Permanent Magnet - Ali, S.; Ikram, J.; Devereux, C. P.; Bukhari, S. S. H.; Khan, S. A.; Khan, N.; Ro, J.-S. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The reduction in cogging torque enables smooth operation and an increase in the torque density of the machine. This research aims to minimize cogging torque in dual rotor single stator axial flux permanent magnet (AFPM) machine. Reduction in cogging torque makes the back EMF sinusoidal and reduces the torque ripples in AFPM machine. In this paper, an elliptical trapezoidal-shaped permanent magnet (PM) is proposed to minimize torque ripples of the AFPM machine. The 3D finite element analysis (FEA) is used for the analysis of AFPM machine. The optimization of AFPM machine is done by employing the asymmetric magnet-overhang along with the parameters of elliptical-shaped PM using Genetic algorithm (GA).